Merkel cell carcinoma in pelvic lymph nodes after surgical staging for endometrial cancer: A case report and review of the literature - Thomakos, N.; Zacharakis, D.; Akrivos, N.; Zagouri, F.; Simou, M.; Bamias, A.; Dimopoulos, M.-A.; Rodolakis, A.; Antsaklis, A. (International Journal of Surgery Case Reports, 2012)
INTRODUCTION: Merkel cell carcinoma (MCC) is a rare malignant neuroendocrine tumor of the skin. PRESENTATION OF CASE: We present a case of MCC in pelvic lymph nodes, revealed after surgical staging for endometrial cancer. A 54-year-old Caucasian woman presented to our department with a threemonth history of postmenopausal bleeding. After proper preoperative evaluation, the patient underwent total abdominal hysterectomy, bilateral salpingo-ophorectomy and pelvic lymph node dissection. The pathology report confirmed the presence of a small, grade I, endometrioid adenocarcinoma and MCC in the pelvic lymph nodes. Primary site of the disease could not been retrieved. The tumor board decided adjuvant chemotherapy (carboplatin and etoposide) and close follow-up every 2 months. Our patient is alive with no evidence of disease 12 months after surgery. DISCUSSION: It is noteworthy that 19% of the patients with MCC had lymph node metastasis with no apparent primary lesion. The mechanism of this regression remains unclear, although a higher apoptotic activity has been observed in MCC than other skin tumors. In addition, other co-malignancies have also been linked to MCC patients. The explanation for the frequent occurrence of other primary neoplasms in patients with MCC is still unclear. However, a reasonable cause could be an altered genetic profile or an immuno-compromised situation in these patients. CONCLUSION: Further analytic investigations are needed to clarify the role of various factors in the spontaneous regression or not of this neuroendocrine tumor as well as in the simultaneous genesis of other primary carcinomas. © 2012 Surgical Associates Ltd.
Keywords: Endometrioid adenocarcinoma; Merkel cell carcinoma; Neuroendocrine tumor; Pelvic lymph nodes